Research on the Symbiotic and Reciprocal Relationship between Yellow River Culture and the Overall Environment in Moral Education during the New Era - Sun, Yaping (Pacific International Journal, 2023)
Abstract:This thesis investigates the symbiotic relationship between the Yellow River culture and moral education’s entire environment, exploring their interaction and mutual influence. It emphasizes the importance of preserving and promoting China’s rich traditional culture, with the Yellow River being of particular significance as the cradle of Chinese civilization. The Yellow River culture, as an integral part of Chinese tradition, embodies spiritual qualities, reverence for nature, and the wisdom of its people. The study aims to analyze the impact of the Yellow River culture on moral education, examine the integration of the entire environment concept within the culture, and explore the symbiotic relationship between the Yellow River culture and the moral education environment. The research methodology involves a literature review and case study analysis, drawing on academic papers and empirical data.Preserving and revitalizing the Yellow River culture is crucial for its development, requiring collaborative efforts from educational and research institutions. Adapting to the digital era, the culture must be disseminated and promoted through new media and technology. Exploring the symbiotic relationship between the Yellow River culture and the moral education environment is essential to understand the interplay and influence among culture, individuals, and the environment. The study’s findings have practical implications for education, culture, and environmental preservation, enabling the preservation of Chinese traditional culture, fostering environmental awareness, and providing policy recommendations and strategies for cultural construction and environmental protection.